Modelo matemático para a dinâmica populacional do bugio ruivo em um habitat fragmentado - Brizola, Fernando Mazetto (2016)
The brown howler monkey (Alouatta guariba clamitans) is a species threatened with extinction. In an area belonging to the Brazilian army located in the state of Rio Grande do Sul, Brasil, where the highly fragmented landscape is composed by patches of forest, there was a high density of this species. However, an epidemic of sylvatic yellow fever between 2008 and 2009 drastically reduced the population leading it to extinction in some of the patches. This species plays an important role in ghting yellow fever since it can indicate that the yellow fever virus is circulating in the environment. When the virus is identi ed in dead monkeys, the public health agents trigger prevention measures. In this work, we present a simple discrete metapopulation model in order to describe the dynamics of the howler monkey. Through simulations of the proposed model for parameters obtained by Fortes (2008) in an experimental studies developed in this area, we can conclude that the population in an isolated patch with very low density will take around 30 years to recover its carrying capacity. On the other hand, a noncolonized patch can take around 20 years to be recolonized by individuals coming from a close patch.